An Empirical Study of Integrating Information Technology in English Teaching in Artificial Intelligence Era - Huang, Lu (Scientific programming, 2022)
Affordance of information technology in artificial intelligence era is accelerating its increasing integration into English teaching all over the world. However, the implementation of integrating information and communication technology requires the transformation of teaching concepts, the optimization of teaching strategies, and the innovation of teaching methods.This empirical study, which is based on analysis of status quo of college English teaching modes in China, aims to explore pedagogical challeges and motivate English teachers to take initiative to transform their clarssrooms with technology. It further proposes a framework as well as some innovative strategies in implementing the reform in college English classrooms. An exploratory study was conducted using the framework, indicating that integrating information communication technology into education can greaty enhance teaching efficiency, effectively improve learning outcomes, and promote students’ positive attitude towards learning.